Possibilities of verification of a short-term functional outcome prognosis in the acute period of spontaneous supratentorial intracerebral hemorrhage using modified variants of the Intracerebral Hemorrhage Scale - A. A. Kuznietsov (Zaporožskij Medicinskij Žurnal)
The main purpose of the study was to analyze a diagnostic informative value of modified variants of the Intracerebral Hemorrhage Scale as techniques for detecting adverse functional outcome risk in the acute period of spontaneous supratentorial intracerebral hemorrhage (SSICH).